Pengaruh Penerapan Senam Otak (Brain Gym) Terhadap Kepatuhan Proses Belajar Anak Tuna Grahita Di SLB Jati Wiyata Dharma Kabupaten Tuban - Yulia Rahayu Ningsih (Jurnal Keperawatan Olahraga, 2026)
Background: Children with intellectual disabilities experience limitations in intellectual functioning, attention, and memory, which significantly affect their ability to concentrate and comprehend learning materials. Aim:  to examine the effect of a brain gym intervention—a series of simple movements designed to optimize brain function, enhance oxygenation, and improve concentration—on students’ learning compliance. Methods: This research employed a quantitative pre-experimental design using a one-group pretest–posttest approach without a control group. The sample consisted of 19 students from SLB Jati Wiyata Dharma Tuban, selected through purposive sampling. Data were collected using a learning compliance questionnaire administered before and after the intervention and subsequently analyzed using the Wilcoxon signed-rank test. Results:  The results revealed a significance value of 0.0001, indicating that H1 was accepted. These findings demonstrate that brain gym therapy produced a significant change in the learning compliance of children with intellectual disabilities at SLB Jati Wiyata Dharma, Tuban Regency. The results suggest that brain gym is an effective means of fostering a calm and focused learning environment. Conclusion: Therefore, schools are recommended to implement brain gym exercises routinely as an innovative instructional method to enhance focus and discipline among students with special needs.